Cloud-Based ERP Integration in Regional Hospitals: A Critical Analysis Success Factors and Change Management in Indonesia - Wahyu Eko Saputro; Vika Fransisca (Al-Makki Publisher, 2026)
Digital transformation in the public health sector has become increasingly urgent to meet demands for efficiency, transparency, and integrated services. In this context, the implementation of cloud-based Enterprise Resource Planning (ERP) systems represents a strategic solution for Regional Hospitals (RSD) in Indonesia. This study aims to identify the Critical Success Factors (CSFs) and examine the role of change management using the ADKAR model in supporting successful cloud ERP implementation. A qualitative case study approach was employed across several regional hospitals, with data collected through in-depth interviews, field observations, and document analysis. The findings indicate that the success of cloud ERP implementation is strongly influenced by digital readiness, leadership support, user training, and the quality of vendor partnerships. Furthermore, the ADKAR model effectively facilitates the transition process by guiding organizational change from awareness to reinforcement. The implementation also contributes to operational efficiency, including reduced inventory costs, faster HR administrative processes, and improved reporting transparency. However, several challenges persist, such as user resistance, limited sustainable budgets, and disparities in digital infrastructure across regions. This study concludes that successful cloud ERP implementation requires an integrative approach that combines technological, organizational, and human factors to achieve sustainable outcomes in public healthcare systems.